Testing the audit quality of female audit partners: Empirical findings from Thailand - Hadisurja, Andrea Chrysanti; Herusetya, Antonius; Purba, Golrida Karyawati (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: The annual increase in the number of female auditors in partner positions has been particularly pronounced in Southeast Asian countries, with Thailand being a notable example. This study, thus, investigates the quality of female audit partners compared to male audit partners in terms of how clients manage earnings.Design/Methodology/Approach: The researchers hand-collected gender data of audit partners from the audit reports of all listed firms on the Stock Exchange of Thailand and obtained 424 firm-year observations. The researchers applied two models to test the hypotheses, using cross-sectional time-series OLS and logistic regression data analyses. The researchers also performed additional analyses and robustness checks to support the main tests.Research findings: The study revealed no substantial disparity in the female and male auditors’ quality at the partner levels, as measured by accrual earnings management and earnings distribution approaches. The findings indicate that female and male audit partners have similar audit quality in preventing earnings management and earnings benchmark likelihood. The study adds to the existing research in East (Southeast) Asia, showing that female partners in these countries have audit quality that is at least comparable to male partners.Theoretical contribution/Originality: The researchers extend prior studies on the behavior distinction in audit quality of the auditor gender at the partner level, which is under-researched in Southeast Asia.Practitioner/Policy implication: The study has important implications for stakeholders and standard-setters to keep strengthening female leadership in the auditing industry and promoting higher gender parity in the growing industry of the future.